2023
DOI: 10.1002/hsr2.1543
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acceptance, attitude, and knowledge towards artificial intelligence and its application from the point of view of physicians and nurses: A provincial survey study in Iran: A cross‐sectional descriptive‐analytical study

Zeinab Hamedani,
Mohsen Moradi,
Fatemeh Kalroozi
et al.

Abstract: Background and AimsThe prospect of using artificial intelligence (AI) in healthcare is bright and promising, and its use can have a significant impact on cost reduction and decrease the possibility of error and negligence among healthcare workers. This study aims to investigate the level of knowledge, attitude, and acceptance among Iranian physicians and nurses.MethodsThis cross‐sectional descriptive‐analytical study was conducted in eight public university hospitals located in Tehran on 400 physicians and nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The average age of participants was 42.0 years, similar to that of other studies [5][6][7]. 21% of the participants indicated that they have taken courses or training related to AI, a percentage that is slightly higher than in studies conducted in other developing countries such as Iran (2.2%) and India (6.5%), but still not a very high value, suggesting that there is a sufficient need for AI-related education within Pakistan's medical landscape [8,9].…”
Section: Discussionsupporting
confidence: 74%
“…The average age of participants was 42.0 years, similar to that of other studies [5][6][7]. 21% of the participants indicated that they have taken courses or training related to AI, a percentage that is slightly higher than in studies conducted in other developing countries such as Iran (2.2%) and India (6.5%), but still not a very high value, suggesting that there is a sufficient need for AI-related education within Pakistan's medical landscape [8,9].…”
Section: Discussionsupporting
confidence: 74%
“…For instance, some questions about trust and acceptance of clinicians include general perceptions such as the problems one sees regarding the application of AI in medicine ( 11 ) and whether AI would be a burden for practitioners ( 12 ). Other studies report levels of acceptance in a general manner, such as attitudes being “relatively favorable” or an “average” level of acceptance ( 13 ). However, little is known about the extent to which overall assessment of AI is driven by trust, beliefs and attitudes towards AI and how these translate into the acceptance of specific AI tools in clinical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Training and a solid legal framework were suggested to enhance AI adoption in healthcare. Moreover, AI perception among Iranian healthcare workers was investigated (Hamedani et al, 2023). This Iranian study evaluated physicians and nurses' knowledge, attitudes, and acceptance of AI.…”
Section: Literature Reviewmentioning
confidence: 99%